Aktualisasi Nilai-Nilai Pancasila Sila Ke 2 Dalam Upaya Membangun Sikap Adil dan Beradab di Sekolah Dasar Negri Cinunuk 3 Bandung - Syahwa Aulia Fasha; Zahra Amelia Bachtiar; Nayla Azizah; Dini Aulia; Bilqis Ayu Sabrina; Robby Ahmad Maulidi; Afwan Moehtaram; Fauzan Fakhrurozi Kurniawan; Rofi Riyadhoh; Siti Sofiah; Dian Herdiana (Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the implementation of the second principle of Pancasila, “Just and Civilized Humanity,” in the daily activities of 4th- and 5th-grade students at SDN Cinunuk 3. Using a qualitative method through case studies and direct observation, this research explores students’ understanding and practice of humanitarian values, fairness, and civility in their interactions with peers, teachers, and the school environment. The findings show that although students have received instruction on Pancasila, there remains a gap between their conceptual understanding and its application in daily behavior. These results suggest the need to strengthen character education and implement more effective Pancasila learning methods at the elementary school level.